the marketing strategies and their role in increased productivity of the insurance companies: دراسة تطبيقية في شركة التامين العراقية (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Search procedures on the treatment research has tended include what cam followers Astaratejaat available to the business organizations to achieve competitive advantage and continued benefits of the form in which the organization can maintain its success in the race competitive and increase production efficiency. The objectives of the study , the study came with  the number of goals and the most important one the  knowledge of the relationship and the influence between the variables of the study and review of the latest literature frameworks intellectual and philosophical to the variables of the study and come up with recommendations that could help the organization improve its performance . In identifying the importance of the it study came with a number of Values ​​was and the most prominent one was the review of the importance of planning and strategy,  and that why  researcher wanted to review the latest management literature of ideas , concepts, and a statement of inputs and outputs and the importance to the status of marketing strategies  the organization can rely on to improve its performanceAnd then review the latest literature of productivity concepts and how they are measured and their impact on the company's business . the first part, took care of the methodology of research and ensure the second part,  reviewed  the most important terms of the concept and its importance and dimensions of marketing strategy and that the researcher collected . The third section reviewed  the most important terms of efficiency and productivity , relevance and how they are measured and finally the fourth section is the practical application and the review and analysis of company data document in the collection of data depends on the latest Statistics and the annual reports of the company.  finally the study's came up with intellectual and theoretical and applicable conclusions that the diagnosed the truth and the reality of marketing plans and productivity indicators in the company , and the study sample. The study also made ​​recommendations , which were inspired by the conclusions reached by the theoretical and practical study.